Learning management systems for instructional quality assurance in nonformal equivalency education - Tri Assifa Candra Defi; Jamaris Jamaris (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examined learning quality control in PKBM equivalency education programs in Padang City and explored the potential of a Learning Management System (LMS) to strengthen it. Evidence from questionnaires and focus group discussions indicated that while planning and instructional delivery were generally adequate, monitoring of learner engagement, systematic documentation, and data-driven quality improvement remained limited. Quantitative results highlighted gaps between instructional implementation and continuous quality assurance, and qualitative insights revealed fragmented digital practices constrained by partial tool use and varying digital literacy. Respondents expressed a high to very high need for an integrated LMS capable of combining learning delivery, assessment, monitoring, and reporting. Based on these findings, a prototype LMS was designed to address identified gaps and support evidence-based decision-making. This study contributes both practical and theoretical insights by demonstrating how LMS features such as learner activity tracking and automated reporting can operationalize learning quality control in nonformal education contexts.